Β‐Arrestin‐1 directly interacts with Gαs and regulates its function. Issue 5 (23rd January 2013) - Li, Bo; Wang, Congcong; Zhou, Zhaocai; Zhao, Jian; Pei, Gang
Abstract : Gαs physically interacts with Beta‐arrestin‐1 by cross‐linking study (View interaction). Abstract : ► We find β‐arrestin‐1 interacts with Gαs but not Gαi or Gαo . ► β‐Arrestin‐1 binds to Gαs in a rapid kinetic mode. ► β‐Arrestin‐1 promotes the binding and release of GTPγS from Gαs in vitro. ► The interaction deficient mutant β‐arrestin‐1 L33K has no detectable effects on the Gαs function.